2021
DOI: 10.1371/journal.pone.0261584
|View full text |Cite
|
Sign up to set email alerts
|

The association between educational level and multimorbidity among adults in Southeast Asia: A systematic review

Abstract: Background In Southeast Asia, the prevalence of multimorbidity is gradually increasing. This paper aimed to investigate the association between educational level and multimorbidity among over 15-years old adults in Southeast Asia. Methods We conducted a systematic review of published observational studies. Studies were selected according to eligibility criteria of addressing definition and prevalence of multimorbidity and associations between level of education and multimorbidity in Southeast Asia. The Newca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…However, the researchers also found that the prevalence increased in people with university/college degrees. It aligns with a review study in Indonesia that multimorbidity cases would increase along with their education level [4].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, the researchers also found that the prevalence increased in people with university/college degrees. It aligns with a review study in Indonesia that multimorbidity cases would increase along with their education level [4].…”
Section: Discussionsupporting
confidence: 78%
“…Lowand middle-income countries (LMICs) were estimated to have a multimorbidity prevalence of 10-11%, which is predicted to increase in the coming years. The prevalence of multimorbidity in Southeast Asia also gradually increases from 4.5% at the beginning of the 21st century to about 10% in recent years [4]. In addition, the prevalence of multimorbidity, the coexistence of two or more chronic diseases, is expected to increase, including in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that having tertiary education decreased the odds of multimorbidity, this has been noted both locally and internationally [ 19 , 20 , 52 ]. However, a systematic review of education levels and multimorbidity in Southeast Asia found the association was inconsistent [ 53 ]. This study found that being employed decreased the odds of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that increased fear and anxiety are connected to high blood pressure [ 54 , 55 ]. A recent systematic review of 18 studies conducted in Southeast Asia reported mixed associations between education and chronic diseases related to multimorbidity [ 56 ]. Considering such fluctuating evidence, further studies are required to better understand the association between educational status and the prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 99%